2020
DOI: 10.3390/en13030519
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Structural Damage in Low Permeability Coal Material of Coalbed Methane Reservoir under Cyclic Cold Loading

Abstract: The pore and fracture structure of coal is the main factor that affects the storage and seepage capacity of coalbed methane. The damage of coal structure can improve the gas permeability of coalbed methane. A coal sample with a drilled hole was kept inside of a custom-designed device to supply confining pressure to the coal sample. Liquid nitrogen was injected into the drilled hole of the coal sample to apply cyclic cold loading. Confining pressures varying from 0~7 MPa to the coal sample were applied to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Table shows the number of research articles on LN 2 fracturing by country according to SCI. China, the United States, Australia, and Japan are the countries that have published the greatest number of articles. …”
Section: Ln2 Fracturing Technology Developmentmentioning
confidence: 99%
“…Table shows the number of research articles on LN 2 fracturing by country according to SCI. China, the United States, Australia, and Japan are the countries that have published the greatest number of articles. …”
Section: Ln2 Fracturing Technology Developmentmentioning
confidence: 99%
“…Moreover, researchers can acquire comprehensive insights into the mechanical properties and fracture evolution of rocks by employing diverse testing methods and techniques, including rock mechanics experiments and observations using a fault microscope. These approaches enable the detailed examination of the rock's mechanical characteristics and the progression of fractures [15]. According to Kaiser's research, significant acoustic emission phenomena occur only when the metal specimen is subjected to loading again after unloading, and only when the stress reaches the maximum stress previously applied.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments have also found that the permeability of coal subjected to LN 2 cooling can be improved. The elastic modulus, compressive strength, and tensile strength of coal subjected to LN 2 cryotherapy decrease significantly, and the fracture propagation becomes more active during the mechanical experiments due to changes in the internal structure after the LN 2 -cooling treatment. However, there is relatively little information about the effect of LN 2 cooling on tight gas sandstone rocks.…”
Section: Introductionmentioning
confidence: 99%